SULT1A1 (Minoxidil Sulfotransferase) enzyme booster significantly improves response to topical minoxidil for hair regrowth. (25th June 2021) - Dhurat, Rachita; Daruwalla, Sanober; Pai, Suraj; Kovacevic, Maja; McCoy, John; Shapiro, Jerry; Sinclair, Rod; Vano‐Galvan, Sergio; Goren, Andy
Abstract: Background: Minoxidil is a widely used over‐the‐counter topical treatment for hair loss. The response rate for topical minoxidil is relatively low. Minoxidil is a pro‐drug, converted to its active form, minoxidil sulfate, by SULT1A1 enzymes located in the scalp. Recently, a novel topical formula that increases the activity of SULT1A1 in hair follicles was reported. Aims: To evaluate any benefit of applying the SULT1A1 enzyme booster prior to daily 5% minoxidil treatment. Methods: Male androgenic alopecia patients were recruited to a randomized blinded placebo‐controlled study. Patients were randomized to receive 5% topical minoxidil plus the novel formula or minoxidil plus a sham adjuvant. Patient's hair growth was monitored using global photography over 60 days. Results: Twenty‐four males with androgenic alopecia (Norwood scale average 4.4, range 2–6) were randomized and completed the trial: 12 in the active arm and 12 in placebo. 75% of the subjects who used the SULT1A1 adjuvant with their daily minoxidil treatments for 60 days regrew hair versus 33% of those using the placebo adjuvant ( p  = 0.023). Conclusions: In a small cohort of androgenetic alopecia men, adding the SULT1A1 adjuvant to their daily minoxidil treatment regimen improved hair regrowth.